Annotations on key information from a literature review on the links between diverse economies, biocultural diversity and assemblages of more-than-human relations - Ortiz-Przychodzka, Stefan (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
This document presents the author's annotations based on a literature review depicting conceptual links between diverse economies, biocultural diversity, and assemblages of more-than-human relations. The annotations are related to a coding structure that supported the data analysis presented in the author's PhD thesis "Economies of honey at the agrarian commodity frontier. How diverse economies emerge from the territorial fractures in the Bolivian Chiquitanía".
Analysis of text documents
Literature analysis / Systematic review
Keywords: Literatur; Review; Bioökonomie; Diversität; Wirtschaft; Sozial-ökonomisches System; Sozial-ökologisches System; Biodiversität; Kulturelle Diversität; Werte; Umwelt; Landwirtschaft; Nachhaltigkeit; Mensch-Natur-Beziehungen; Wissensanwendung; Literature; Review; Bioeconomy; Diversity; Economy; Social-economic System; Social-ecological System; Biodiversity; Cultural Diversity; Values; Environment; Farming; Sustainability; Human-Nature Relations; Knowledge Practice